2014
DOI: 10.1152/ajprenal.00012.2014
|View full text |Cite
|
Sign up to set email alerts
|

A knowledge base of vasopressin actions in the kidney

Abstract: Biological information is growing at a rapid pace, making it difficult for individual investigators to be familiar with all information that is relevant to their own research. Computers are beginning to be used to extract and curate biological information; however, the complexity of human language used in research papers continues to be a critical barrier to full automation of knowledge extraction. Here, we report a manually curated knowledge base of vasopressin actions in renal epithelial cells that is design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…Next we used the spreadsheet to generate a Hyper Text Markup Language (HTML) file, as previously described in the Appendix of Sanghi et al. (). This was placed on a publicly accessible web server at https://helixweb.nih.gov/ESBL/Database/Osmo/.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next we used the spreadsheet to generate a Hyper Text Markup Language (HTML) file, as previously described in the Appendix of Sanghi et al. (). This was placed on a publicly accessible web server at https://helixweb.nih.gov/ESBL/Database/Osmo/.…”
Section: Methodsmentioning
confidence: 99%
“…We constructed each database entry to conform to English grammar syntax and to read from left to right as <subject> <verb phrase><object><prepositional phrase><parenthetical information>. Next we used the spreadsheet to generate a Hyper Text Markup Language (HTML) file, as previously described in the Appendix of Sanghi et al (2014). This was placed on a publicly accessible web server at https://helixweb.nih.gov/ESBL/Database/ Osmo/.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hormones are key regulators of sodium transport in the kidney and in ASDN specifically. In addition to the RAAS, it was shown that arginine vasopressin (AVP) (Ecelbarger et al, 2000; Mironova et al, 2012; Stockand, 2012; Bankir, Bouby, & Ritz, 2013; Bankir et al, 2013; Sanghi et al, 2014), atrial natriuretic peptide (ANP) (Kudo & Baird, 1984; Wang et al, 2006; Guo, Alli, Eaton, & Bao, 2013) and insulin (alongside with Insulin-like growth factor 1, IGF-1) (Blazer-Yost, Liu, & Helman, 1998; Li et al, 2013; Ilatovskaya, Pavlov, Levchenko, & Staruschenko, 2013; Pavlov et al, 2013a) are critical modulators of ENaC activity. The kallikrein-kinin systems through its peptide bradykinin also play a specific role in blunting ENaC activity, particularly under conditions of elevated sodium intake (Zaika, Mamenko, O'Neil, & Pochynyuk, 2011; Mamenko, Zaika, Doris, & Pochynyuk, 2012; Mamenko, Zaika, & Pochynyuk, 2014).…”
Section: Regulation Of Sodium Reabsorption – Role Of Enacmentioning
confidence: 99%